2004
DOI: 10.1007/s00213-003-1764-8
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine improves delayed recognition in schizophrenic patients

Abstract: These results suggest that nicotine enhances delayed recognition memory in schizophrenic patients who smoke, but that similar performance enhancement is not observed for working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 44 publications
2
57
1
Order By: Relevance
“…There was also a greater reduction in false alarms in subjects with schizophrenia compared with controls on a verbal memory task performed in a subset of our sample with no improvement in hit rate or source memory (Weiss et al, 2006). These findings are consistent with those of Myers and coworkers who reported that nicotine nasal spray reduced false alarms in smokers and nonsmokers with schizophrenia on a delayed recognition task, although this was also accompanied by a reduction in hit rate in the nonsmokers not seen in the present study (Myers et al, 2004).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There was also a greater reduction in false alarms in subjects with schizophrenia compared with controls on a verbal memory task performed in a subset of our sample with no improvement in hit rate or source memory (Weiss et al, 2006). These findings are consistent with those of Myers and coworkers who reported that nicotine nasal spray reduced false alarms in smokers and nonsmokers with schizophrenia on a delayed recognition task, although this was also accompanied by a reduction in hit rate in the nonsmokers not seen in the present study (Myers et al, 2004).…”
Section: Discussionsupporting
confidence: 94%
“…There is increasing evidence that nAChR stimulation has beneficial effects on cognitive function in schizophrenia, possibly via presynaptic modulation of dopamine and/or glutamate release (McGehee et al, 1995;George et al, 2000;Picciotto et al, 2000;Wonnacott et al, 2000). The administration of both short-and long-acting preparations of nicotine to individuals with schizophrenia has been associated with improved neuropsychological performance (Levin et al, 1996b;Depatie et al, 2002;Smith et al, 2002Smith et al, , 2006Harris et al, 2004;Jacobsen et al, 2004;Myers et al, 2004). Acute administration of the selective a7nAChR partial agonist, DMXB-A, improved P50 gating compared with placebo (Olincy et al, 2006) and administration of the nAChR antagonist, mecamylamine, blocked smoking-associated improvements in performance on attentional and visuospatial working memory (VSWM), implying that nAChR activation mediates smoking-related cognitive enhancement (Sacco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, nicotine gum has no effect in either smokers or nonsmokers on working memory or visuospatial memory [77]. Finally, nicotine nasal spray enhances verbal memory [78], visuospatial delayed recognition [79] and complex reaction times but has no effect on simple reaction times attention or working memory [74,80,79]. Thus, chronic exposure to nicotine in smokers, the mode of experimental nicotine delivery, the nicotine dose given, the particular neuropsychological test, clinical diversity and potentially other factors in these studies may account for the variability of these findings.…”
Section: α7 In Learning and Memorymentioning
confidence: 97%
“…This was accompanied by enhanced activation in the cingulate cortex and thalamic nuclei. In a complementary fashion, nicotinic blockade caused significant deficits in the N-back task [91].. Nicotine nasal spray has been shown to improve spatial organization and also improve memory in people with schizophrenia [92,93]. Nicotine also improves eye tracking, memory and attentional function in schizophrenia [84,85,88,92].…”
Section: The Potential Of Nicotinic Treatment For the Cognitive Impaimentioning
confidence: 99%
“…In a complementary fashion, nicotinic blockade caused significant deficits in the N-back task [91].. Nicotine nasal spray has been shown to improve spatial organization and also improve memory in people with schizophrenia [92,93]. Nicotine also improves eye tracking, memory and attentional function in schizophrenia [84,85,88,92]. Nicotine skin patch treatment in healthy volunteers significantly improved the speed of pre-attentive sensory processing as indexed by mismatch negativity to auditory stimuli in an oddball paradigm [94] Specific nicotinic receptors may be more promising for the improving aspects of cognition in people with schizophrenia .…”
Section: The Potential Of Nicotinic Treatment For the Cognitive Impaimentioning
confidence: 99%